Competitive swimmers and their unconscious body image - Comyn, N. (First international symposium sciences and practices in swimming, 2006)
This clinical and psychoanalytic study conducted among national level swimmers underlines the link between practice and unconscious body image. Through the swimming practice, the subject is both separated from the mother and connected to her by an unconscious bond, therefore the body image becomes fragile. Moreover, achieving a performance induces changes in the body image. These changes occur either before the performance or subsequently, and they modify the subject's psychic functioning. This can be taken into account both by the coach who is targeting the performance and by the sport psychologist when he is providing help.